Bahasa Agama dalam Wacana Sosiologi Agama - Audah, Ali (LP2M IAIN Palangka Raya, 2015)
A short study of the history of the sociology of religion is enough to show the importance of religion as a factor relevant to the study of variations, maintenance , language policy and planning are already equipped to work at least some of them are generally regarded as the founder of a branch of linguistics . However , these effects do not stop merely linguistic region but also on the dimensions of the broader culture . Claiming Arabic is the only language of Islam becomes simpler if it is associated with the contestation countries that historically have been quite dominant in the development of Islam . As a sociological study of religion , it has become wide open land research to continue to be observed in the level of practice speaking societies where Islam is the majority religion